A switchable bandstop-to-bandpass reconfigurable filter for cognitive radio applications. Issue 4 (23rd June 2016) - Nachouane, Hamza; Najid, Abdellah; Tribak, Abdelwahed; Riouch, Fatima
Abstract : This paper presents a simple reconfigurable bandpass filter switching from 2.4 to 5 GHz based on PIN diodes. The proposed filter is intended to add frequency-tunability to antenna systems used in cognitive radio applications. It consists of a bent connecting stub with two open-circuited quarter-wave stubs grounded via PIN diodes. By controlling the didoes states, the electrical length of the stubs can be switched from quarter-wave to half-wave and vice versa, so as to tune the filter center frequency. The proposed design approach consists of ensuring communication at 2.4 GHz while blocking the 5 GHz band in the ON state, whereas in the OFF state, the filter is intended to reject the 2.4 GHz band and passing the 5 GHz band. A prototype of the proposed filter is fabricated and measured to validate the proposed concept. Both simulated and measured results show a two-state filter with a wide tuning range from 2.4 to 5 GHz and a good stopband rejection level better than 40 dB . Moreover, a flat group delay of about 0.55 – 0.7 ns is achieved within the operating bandwidth in both states. The proposed filter is able to achieve simultaneous bandwidth and frequency control, showing an important tool to meet modern system requirements.